2000
DOI: 10.2169/internalmedicine.39.1027
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Anti-anginal Drugs in the Treatment of Angina Pectoris Associated with Silent Myocardial Ischemia. Importance of Quantitative Holter ECG Data for Patient Activity.

Abstract: MethodsWe evaluated the clinical efficacy of transdermal nitroglycerin (NTG-TTS), a patch application of a nitrate, in the treatment of 27 patients with angina pectoris who had asymptomatic myocardial ischemic (SMI) attacks, using a double-blind cross-over method. Evaluation was made using Holter ECGand patient activity data.Results In frequency and duration of continuation of SMIepisodes, no significant differences were noted between the observation and placebo treatment periods, while the values of both thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…A method was developed for counting characteristic walking motions using the accelerometer and converting these data into a walk rate per minute. A heart rate loop with the ST segment was recorded for each period of walking, and the myocardial ischemic threshold was defined as the HR at the point that ischemic ST depression began, with a simultaneous recording of the walking rate (13)(14)(15)(16). Variation of HR at the ischemic threshold over 24 hours was demonstrated by linear regression analysis of these data.…”
Section: Methodsmentioning
confidence: 99%
“…A method was developed for counting characteristic walking motions using the accelerometer and converting these data into a walk rate per minute. A heart rate loop with the ST segment was recorded for each period of walking, and the myocardial ischemic threshold was defined as the HR at the point that ischemic ST depression began, with a simultaneous recording of the walking rate (13)(14)(15)(16). Variation of HR at the ischemic threshold over 24 hours was demonstrated by linear regression analysis of these data.…”
Section: Methodsmentioning
confidence: 99%
“…The resulting values were regarded as the parasympathetic or sympathetic tone, respectively. The number of steps taken over 15 minutes was determined by conversion of accelerometer sensor values into the number of steps using a method developed in-house (7,8). Hf, L/H, and the number of steps were plotted against systolic pressure on an X-Y co-ordinate, and the correlation coefficient was determined by the linear least squares method.…”
Section: Ambulatory Blood Pressurementioning
confidence: 99%
“…Therefore, the conventional concept requires re-examination, but clinical studies of this issue have yet to be reported. Here, we propose a new classification method based on the evaluation of ambulatory blood pressure using frequency analysis of the RR interval in simultaneous ambulatory blood pressure monitoring and Holter ECG recording, and we consider the clinical significance of data obtained from this new approach (6)(7)(8). We investigated the relationship between baroreceptor function and ambulatory blood pressure (as a method for measurement of blood pressure in the chronic phase), and evaluated the effect of baroreceptor function on blood pressure control in the chronic phase.…”
Section: Introductionmentioning
confidence: 99%